The Psychometric Properties of the Norwegian version of Competence and Adherence Scale for Cognitive Behavioral Therapy (CAS-CBT) - Rasmussen, Lene-Mari Potulski; Puggard, Louise Berg (PsykTestBarn, 2019)
Competence and Adherence Scale for Cognitive Behavioral Therapy (CAS-CBT) is an 11-item observation-based measure designed to evaluate therapist adherence and competence in (manual-based) anxiety treatment for youths. The CAS-CBT is a modified version of the Cognitive Therapy Adherence and Competence Scale (CTACS; Barber et al., 2003) developed in Norway by Jon Bjåstad and colleagues (2015). The measure comprises three dimensions; 1) Cognitive therapy structure; 2) Process- and relational skills and 3) Goals for the session. The systematic literature search resulted in a total of 85 references of which two met the inclusion criteria. Both studies were based on Norwegian clinical samples where the instrument was used in effectiveness studies of anxiety in children (7-15 years). The exploratory factor analyses based on one study identified two factors, showing good internal consistency of the instrument. Further, the intraclass-correlations between the expert raters and the students were adequate to excellent for mean scores on Adherence and Competence. Test-retest reliability examined in one study was excellent. Norm data is not relevant for this measure. CAS-CBT has limited psychometric documentation. The results of the reliability analyses varied somewhat, but were mostly good to excellent. The factor analysis suggested another factor structure than implied in the instrument description. It could thus be questioned whether the instrument measures what it is intended to measure. No studies have investigated the construct validity of the measure apart from the exploratory factor analysis. Thus, more research on the psychometric properties of the instrument is needed.